All Days 2008
DOI: 10.2118/116912-ms
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gas, Water, WAG Injections, and Infill Wells for Improving Recovery of One of Iranian Reservoirs

Abstract: Increasing demand for energy has forced oil companies to resort to secondary and tertiary methods to increase the recovery from the existing reservoirs. In this paper, enhancing the recovery factor of one of Iranian reservoirs which is a naturally fractured reservoir was investigated. For this reservoir, it is estimated that 96.5 percent of oil is contained in the matrix and 3.5 percent in the fractures. The field is an undersaturated reservoir with no active gas cap and no strong water aquifer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Field experience has shown that more than 15% incremental oil can be recovered from a waterflooded reservoir by updip gas injection (e.g., Johnston 1988;Carlson 1988;Shahsavari and Dabbous 1991;Langenberg et al 1995;Gunawan and Caié 1999). For high-relief fractured carbonates, updip gas injection to increase oil recovery has been used successfully in Oman and Iran (O'Neill 1988;Novinpour et al 1994;Saidi 1996;Eikmans and Hitchings 1999;Sadooni et al 2008). These field test results are supported by laboratory studies (e.g., Kantzas et al 1988;Blunt et al 1994;Øren and Pinczewski 1995;Ren et al 2003).…”
Section: Increased Oil Recovery Because Of Injection Of Gas For Ugsmentioning
confidence: 77%
“…Field experience has shown that more than 15% incremental oil can be recovered from a waterflooded reservoir by updip gas injection (e.g., Johnston 1988;Carlson 1988;Shahsavari and Dabbous 1991;Langenberg et al 1995;Gunawan and Caié 1999). For high-relief fractured carbonates, updip gas injection to increase oil recovery has been used successfully in Oman and Iran (O'Neill 1988;Novinpour et al 1994;Saidi 1996;Eikmans and Hitchings 1999;Sadooni et al 2008). These field test results are supported by laboratory studies (e.g., Kantzas et al 1988;Blunt et al 1994;Øren and Pinczewski 1995;Ren et al 2003).…”
Section: Increased Oil Recovery Because Of Injection Of Gas For Ugsmentioning
confidence: 77%